Penguatan Kompetensi Konselor dalam Memberikan Layanan Bimbingan dan Konseling Islam - Ermalianti Ermalianti; Willy Ramadan (Alhadharah: Jurnal Ilmu Dakwah, 2022)
This article will describe strengthening the competence of counselors in providing Islamic counseling guidance services. The research method used is literature study with documentation as a data collection technique. The result of research found that a counselor‘s competence becomes the indicator for carrying out an effective counseling. A competent counselor will gain trust from his/her client so they eventually decide to get helps from the counselor. This competency is also required to make the process of counseling becomes more efficient. Because of its importance, it is necessary for counselors to develop their counseling competences. In addition, in giving Islamic guidance and counseling, which is carried out based on the basis of Quran and Hadist, the competence is a must for helping the clients aware of their potentials and nature. Islamic morality becomes the footing of an Islamic counselor in helping the client solve the problems of his life. This makes the clients have an awareness of the urgency of religion that is more than just a guide to worship, but also a solution in life. By cultivating a consensual belief in Islamic counseling becomes a means to preach related to religious perfection. Therefore, the competence of counselors must always be improved.